Glomus Tumour: a retrospective review of 15 years. experience in a single institution - Fazwi, R.; Chandran, P.A.; Ahmad, T.S. (Malaysian Orthopaedic Association, 2011)
Glomus tumours (GT), neoplasms of the glomus body comprise 4.5% of upper limb tumours. Seventy-five per cent of these occur in the hand, and most are subungual (50%). We performed a literature review and retrospective search of histopathologically confirmed GT seen from 1995 to 2009. Fifteen patients were identified, with an average age of 49.6 years. Eight were in the hand, 2 in the upper limb, 2 lower limb and 3 in the ear. Eighty-six per cent presented with pain and 50% underwent radiological investigation. Most diagnoses followed biopsy findings. Surgical excision resulted in a recurrence rate of 13%. The average time to diagnosis was 3.3 years. The average duration of symptoms was 7 to 11 years with an average of 2 to 3 consultations pre-diagnosis. MRI remains the most useful imaging modality (82 to 90% sensitivity). Excision biopsy is the most common treatment. Greater awareness is needed for quicker diagnosis.